Financial statement analysis - Ayush Shah (Zebra Learn, 2023)
"Numbers never lie" is a well-known saying, but it's essential to understand how to interpret them to gain crucial information for your finance career. In the world of finance, the decisions you make can have high stakes, whether you're investing in a company, acquiring a business, giving a loan, or going for an IPO. That's why financial analysis is so vital - it helps you make informed decisions based on hard facts instead of guesses. Zebralearn's step-by-step guide covers the entire financial analysis process, from data extraction to financial statement interpretation, enabling you to make sound decisions.This book is an excellent resource for anyone interested in building a career in finance, including CA, CFA, MBA students, professionals. This book is easy to understand and ideal for those with no prior finance knowledge, making it perfect for finance career builders and investors. The well-structured learning path ensures that you'll master financial analysis in no time. The book is 100% actionable, with no theory, and it includes a comprehensive curriculum covering balance sheets, income statements, cash flow statements, and more. Don't guess when it comes to finance - start analyzing with this comprehensive guide to financial analysis.
Keywords: Accounting